Strategi Pemasaran Inklusif: Dampak Komunitas LGBTQ+ terhadap Persepsi Merek dan Penjualan di Perusahaan Kate Spade New York - Clarisa; Puspita, Dewi; Wijaya, Vallencia; Cristy, Viola (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research discusses an inclusive marketing strategy that involves LGBTQ+ in the Kate Spade New York fashion brand. Through a quantitative research method with a literature review approach, this study aims to investigate the building of brand image, the impact that appears, and the public's perception of this initiative. In the background, it is known that fashion has undergone significant changes from time to time. In the early 2000s, fashion was still highly compartmentalized by gender, but this perception has changed over the years. The LGBTQ+ community has also become an important part of the world of fashion and marketing. It can be seen that Kate Spade New York, one of the leading fashion brands, has shown support for the LGBTQ+ community through her Rainbow Shop collections and partnerships with organizations such as The Trevor Project. However, there is no clear information regarding changes in brand perception and sales after Kate Spade New York supports LGBTQ+. Even though this brand has the support of the LGBTQ+ community, there has been negative feedback from some quarters. Therefore, it is important for brands to continue to strengthen their commitment, conduct in-depth market research, and communicate clearly and authentically about their values of inclusion. Keywords: LGBTQ+, Inclusive Marketing Strategy, Brand Perception, Sales